Ensamblajes activistas: feminismos y revuelta social en Chile (2022)
This article presents a theoretical proposal for new times of activism in Chile. It purpose is to build a current analysis on the development of feminist movements in the last decade, considering their strengthening and expansion processes as a relevant transformative and purposeful critical social force, which has stood out as a participant, actor and co-constructor of the recent processes of popular revolt in the context of the so-called social outburst that began in October 2019, in the constituent process and in the face of the difficulties posed by the pandemic. Based on the concepts of discursive fields of action and assemblages, it proposes to understand the new relationships, spaces and events of protests comprised by the feminist field in its interactions with other actors and contemporary social movements in Chile, as activist assemblages that, in their actions and from their interactions, create emergent, new, different properties that only occur under these assemblages. This represents a “true becoming” with great political potential —creative and conflictive— from which to think about current Chilean society.